Book Review: Social Marketing in India - Mundanad, Manjari (Prabandhan: Indian Journal of Management, 2015)
The present book review is of the book - Social Marketing in India written by Sameer Deshpande and Nancy R. Lee. Usually, social marketing is confused with social media marketing, but both these terms differ from each other. The book has explained the concept of social marketing and its application not just in healthcare, but also in other public health-related services. The book also talks about non healthcare services as that of poverty, illiteracy, its pros and cons. The book has discussed about the concept of social marketing in the Indian context by using various cases of Indian origin. The book would be useful to the professionals all around and the government to know the challenges involved in social marketing and how to overcome these challenges by using various social marketing strategies as discussed in the book.